2014
DOI: 10.5455/ijmsph.2014.110720142
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of post natal care in tribal area of Madhya Pradesh, India: A community based cross-sectional study

Abstract: Background: Postnatal period is a vulnerable time, because most maternal and new born deaths occur during this period, especially immediately after childbirth. Postnatal care in the first hours and days after childbirth could prevent the great majority of these deaths. Aims & Objectives: Present study was conducted with the objective to assess the utilization of post natal care and associated factors in tribal area of Madhya Pradesh. Materials and Methods: A community based cross-sectional study carried in tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 17 publications
2
22
3
Order By: Relevance
“…10 Hence, observations of our study are more or less consistent with that of Kotresh et al and Joshi et al 13,20 While, we found more percentage of mothers availing benefits of post-natal services than those found by other studies. 12,15,17,18 However, Parineeta et al reported more percentage of mothers who completed 3 postnatal visits than present study. 10 The findings depict that advice for contraceptive and family planning is given to 94.26% of mothers.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…10 Hence, observations of our study are more or less consistent with that of Kotresh et al and Joshi et al 13,20 While, we found more percentage of mothers availing benefits of post-natal services than those found by other studies. 12,15,17,18 However, Parineeta et al reported more percentage of mothers who completed 3 postnatal visits than present study. 10 The findings depict that advice for contraceptive and family planning is given to 94.26% of mothers.…”
Section: Discussioncontrasting
confidence: 51%
“…17 According to Sharma et al, 67.6% received first postnatal care within 24 hours of delivery. 18 Thus, percentage of mothers receiving immediate postnatal care is far more in present study than that reported by other studies. [16][17][18] In urban area 58.33% mothers received 3 or more postnatal visits, while 3.3% did not receive a single postnatal visit.…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations